Comparative performance analysis of building foundation Ground heat exchanger - Kayaci, Nurullah; Demir, Hakan (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
The aim of this work is to improve the performance of Ground-Source Heat Pumps (GSHPs) by placing the heat exchanger pipes in the soil under the building foundation and in the building foundation reconstructed in Turkey. In this scope, firstly, experimental studies have been performed on horizontal parallel pipes buried in soil under the foundation of the 2400 m(2) Central Laboratory building, which was newly built at Yildiz Technical University. A comparison between the results of the experimental and newly developed numerical model is presented. Then, a full-scale numerical model for a shopping mall is developed based on the pipe location (soil and concrete layer), Numbers of Parallel Tube (NPTs) and different condensation temperatures in the heating season. The results show that the COP of GSHP when the pipes are buried in the soil under the building foundation is greater than when the pipes are buried in the building foundation. Furthermore, considering capital investment and operational costs, a reference function is defined as an optimization parameter. The effects of the pipe location, increasing rates in electricity prices and NPTs on reference function are investigated. For higher NPT values, locating the pipes in the foundation gives higher values of the reference function while for lower NPT values it is vice versa.
Keywords: Ground source heat pump; Building foundation; COP; Optimization; Economic analysis; BURIED PIPE; PUMP SYSTEM; MODEL; Energy & Fuels; Geology